(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
According to the present survey the family of Eriococcidae contains 628 species (the ScaleNet database contains only 572 species on 24 February, 2009) of 97 genera. The description of new genera and species of Eriococcidae have been increasing steadily since 1758 till present. The family has highest numbers of genera and species in the Palaearctic Region, followed by the Neotropical, Australian, New Zealand and Pacific regions, and finally by the Nearctic region. The very poor representation in the Ethiopian, Austro-Oriental and Oriental regions is remarkable. The number of endemic species is especially high in the Palaearctic, Australian, New Zealand and Pacific regions. In the Palaearctic and Nearctic regions the eriococcid fauna on herbaceous and grass is rich. Although the gall forming species on Myrtaceae especially on Eucalyptus are extremely numerous in Australia, the Fagaceae harbour a lot of species in New Zealand and Australia. The Venn diagram shows that all zoogeographic regions have clearly separated specific eriococid faunas at both generic and species levels. We found the strongest connection between the Oriental and the Palaearctic regions which have in common 5 genera and 20 species. There is some weak connection between the Nearctic and Palaearctic as well as the Nearctic and Neotropic regions.The Oriental andAustro-Oriental regions are connected by species of Gossypariella and Sangicoccus. The Australian Region is connected with the New Zealand and Pacific regions by the Madarococcus species. The morphological similarity of Pseudomontanococcus from the Austro-Oriental region and Montanococcus from New Zealand present a new possible connection between these regions. New Zealand has some connection with the Neotropical Region, too. Some genera show unusual distribution, Cryptococcus is present in the Palaearctic, and Nearctic regions, and in New Zealand, with more species in the Palaearctic region. The case of Kuwanina shows a similar picture: it has species in Australia, New Zealand and in Palaearctic regions. Both genera may present an old stock of the Acanthococcidae family group. The particular species richness of the Australian and New Zealand regions is in accordance of Hoy’s (1962) view suggesting that the roots of this family and family group may lead under the ice cover of Antarctica. The main evolution of this family occurred there and only subsequently spread to the more temperate regions. Hoy (1962) believed that Eriococcidae originated in the temperate areas of the Gondwana continent and the new data support this opinion. The arid climate and sclerophyllous plants explain the generic and species richness of this family. The present day generic and species composition is formed basically by extinction and vicariance, and less by dispersion.